Novel device for simultaneous volumetric and x-ray diffraction measurements on metal-hydrogen systems - Talagañis, Basilio Andres (2009)
Hydrogen storage materials can form more than one hydride phase. These different phases, in turn, display different hydrogen absorption/desorption capacities, kinetics, and stabilities. Studies aimed at characterizing and improving these materials usually need to correlate hydrogen intake with the precise determination of the hydride phase involved in the process. Here, we present a device designed to perform measurements of well known volumetric techniques with simultaneous x-ray diffraction on the material under study. The compact design can stand up to 6000 kPa of internal pressure while the sample can be heated up to 450 °C. The design process was assisted by finite element modeling and by the use of mock-up prototypes in order to optimize the thermal and under load behaviors. We provide two examples of use for this new device: (1) hydride decomposition in LaNi5 at 115 °C and (2) formation of MgCo during the programmed thermal desorption of the Mg2 CoH5 hydride.